Carbon180 : choosing a winning strategy for carbon removal - Isaacs, Andrew M., (SAGE Business Cases., 2019)
Carbon180's co-founders are at a crossroads in reassessing their organization's future strategy and vision to drive a new carbon-conscious economy. Because Noah Deich and Giana Amador believe that 'big challenges require big thinking,' they have taken a multisector approach towards climate change solutions, working in business, policy, and research. This has resulted in some wins while at the same time challenging the resources of their small organization. Also, their funders recommend tighter focus.Carbon180 must weigh competing strategies to catalyze social change and make key decisions on whether a narrow or broad approach will best achieve the goal of reducing carbon emissions.